Replication slippage of the thermophilic DNA polymerases B and D from the Euryarchaeota Pyrococcus abyssi - Castillo-Lizardo, Melissa; Henneke, Ghislaine; Viguera, Enrique (Frontiers in Microbiology, 2014)
Replication slippage or slipped-strand mispairing involves the misalignment of DNA strands during the replication of repeated DNA sequences, and can lead to genetic rearrangements such as microsatellite instability. Here, we show that PolB and PolD replicative DNA polymerases from the archaeal model Pyrococcus abyssi (Pab) slip in vitro during replication of a single-stranded DNA template carrying a hairpin structure and short direct repeats. We find that this occurs in both their wild-type (exo+) and exonuclease deficient (exo-) forms. The slippage behavior of PabPolB and PabPolD, probably due to limited strand displacement activity, resembles that observed for the high fidelity Pyrococcus furiosus (Pfu) DNA polymerase. The presence of PabPCNA inhibited PabPolB and PabPolD slippage. We propose a model whereby PabPCNA stimulates strand displacement activity and polymerase progression through the hairpin, thus permitting the error-free replication of repetitive sequences.